The book of Postfix : state-of-the-art message transport - Hildebrandt, Ralf (No Starch Press, 2005)
Developed with security and speed in mind, Postfix has become a popular alternative to Sendmail. The Book of Postfix is a complete guide to Postfix whether used by the home user, as a mailrelay or virus scanning gateway, or as a company mailserver. Practical examples show how to deal with daily challenges like protecting mail users from SPAM and viruses, managing multiple domains, and offering roaming access.